2009
DOI: 10.1016/j.nbd.2009.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Viral-like brain inflammation during development causes increased seizure susceptibility in adult rats

Abstract: Viral infections of the CNS and their accompanying inflammation can cause long-term neurological effects, including increased risk for seizures. To examine the effects of CNS inflammation, we infused polyinosinic: polycytidylic acid, intracerebroventricularly to mimic a viral CNS infection in 14 day-old rats. This caused fever and an increase in the pro-inflammatory cytokine, interleukin (IL)-1β in the brain. As young adults, these animals were more susceptible to lithium-pilocarpine and pentylenetetrazol-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 101 publications
1
81
0
Order By: Relevance
“…Epidemiological analyses have also demonstrated that these viral infections often lead to development of persistent epilepsy after infection is resolved (61)(62)(63)(64). Galic and colleagues (2009) showed that neonatal exposure to poli(I:C) increased susceptibility to seizures and memory deficits in adult rats, and that these behavioral changes were associated to neuroinflammation and an increased hippocampal expression of NMDA receptors (65). The results reported in our study indicate that even normocephalic ZIKV-exposed infants might be at increased risk .…”
Section: Cc-by-nc-ndsupporting
confidence: 62%
“…Epidemiological analyses have also demonstrated that these viral infections often lead to development of persistent epilepsy after infection is resolved (61)(62)(63)(64). Galic and colleagues (2009) showed that neonatal exposure to poli(I:C) increased susceptibility to seizures and memory deficits in adult rats, and that these behavioral changes were associated to neuroinflammation and an increased hippocampal expression of NMDA receptors (65). The results reported in our study indicate that even normocephalic ZIKV-exposed infants might be at increased risk .…”
Section: Cc-by-nc-ndsupporting
confidence: 62%
“…In this context, experiments in animal models show that epileptogenic brain injuries (e.g., trauma, hypoxia/ischemia), mimicking bacterial or viral infections (Galic et al 2008(Galic et al , 2009Riazi et al 2010;Stewart et al 2010), or recurrent seizure activity per se (Vezzani et al 2011c) can induce a prominent innate immunity response in glia, which activates rapid and self-perpetuating inflammatory processes in brain tissue (Aronica et al 2012b;Vezzani et al 2013a,b). Notably, this innate immunity response has a significant role in experimental seizure generation, cell loss, and comorbidities developing in the animals.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, neuronal degeneration is observed likely due to increases of PICs [24,25]. For example, IL-1β can increase seizure susceptibility in rat brains [26]. Intracerebral injection of a high dosage of IL-1β results in limbic seizures in wild type mice, but not in transgenic mice with deficient IL-1β receptors [27].…”
Section: Discussionmentioning
confidence: 99%